2012
DOI: 10.1021/jp300709w
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study of the Mechanical Behavior of Individual TiS2 and MoS2 Nanotubes

Abstract: Similar to carbon, several transition-metal chalcogenides are able to form tubular structures. Here, we present results from systematic theoretical investigations of structural and mechanical properties of MoS2 and TiS2 nanotubes in comparison to each other, to carbon nanotubes, and to corresponding experimental results. We have obtained the nanotube’s Young’s moduli (Y), Poisson ratios (ν), and shear moduli (G) as functions of diameter and chirality, using a density-functional-based tight-binding method. Addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
83
1
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 123 publications
(104 citation statements)
references
References 58 publications
14
83
1
3
Order By: Relevance
“…This makes the WS 2 layers pretty rigid, with interlayer spacing of 6.23 Å; it is no wonder that the elastic energy for WS 2 (MoS 2 ) nanotube formation is appreciably larger than that of graphitic carbon. If one takes the elastic energy threshold for folding to be 0.05 eV/atom, the calculated diameter of a single-wall carbon nanotube is between one and 1.2 nm [25], and that of a single-wall MoS 2 should be 6.2 nm [9,26]. Therefore, the diameters of the daughter WS 2 nanotubes observed in the current series of experiments reconcile very well with the previous calculations.…”
Section: Scanning and Transmission Electron Microscopy Analysissupporting
confidence: 87%
“…This makes the WS 2 layers pretty rigid, with interlayer spacing of 6.23 Å; it is no wonder that the elastic energy for WS 2 (MoS 2 ) nanotube formation is appreciably larger than that of graphitic carbon. If one takes the elastic energy threshold for folding to be 0.05 eV/atom, the calculated diameter of a single-wall carbon nanotube is between one and 1.2 nm [25], and that of a single-wall MoS 2 should be 6.2 nm [9,26]. Therefore, the diameters of the daughter WS 2 nanotubes observed in the current series of experiments reconcile very well with the previous calculations.…”
Section: Scanning and Transmission Electron Microscopy Analysissupporting
confidence: 87%
“…Young's modulus has been calculated from the second derivative of the total energy E with respect to the strain ε at the equilibrium volume V 0 [31,32]. …”
Section: Resultsmentioning
confidence: 99%
“…For example, as a similar structural orientation to the SnSe 2 nanotube, a recent study reported the Young's modulus of the TiS 2 (1T structure, where the metal atoms are coordinated octahedrally by the sulfur atom as in the case of SnSe 2 ) nanotube reaches 140 GPa· nm. 62 Our area-based Young's moduli of SnSe 2 ANT and ZNT are calculated to be 59 and 57 GPa·nm, respectively. The significant lower values indicate that the SnSe 2 nanotube is softer than the TiS 2 nanotube.…”
Section: Resultsmentioning
confidence: 96%